The first time she drowned - Kletter, Kerry (New York, NY : Philomel Books, an imprint of Penguin Random House LLC, 2016)
Committed to a mental hospital against her will for something she claims she did not do, Cassie O'Malley signs herself out against medical advice when she turns eighteen and tries to start over at college, until her estranged mother appears, throwing everything Cassie believes about herself into question.
Keywords: Self-actualization (Psychology) -- Fiction; Emotional problems -- Fiction; Family problems -- Fiction; Mothers and daughters -- Fiction; Memory -- Fiction; Sex crimes -- Fiction